Development of Learning Evaluation Based on Automatic Assessment through Quizizz Paper Mode to Improve Students’ Natural and Social Sciences Learning Outcomes - Balqis, Ayssyiyah Sintha; Andriani, Aldina Eka (Jurnal Penelitian Pendidikan IPA, 2024)
Class IV teachers have not implemented technology-based learning evaluation. This research aims to develop, test the feasibility and effectiveness of Automatic Assessment-based learning evaluation through Quizizz Paper Mode to improve the cognitive learning outcomes of class IV students. The type of research used is Research and Development with the Borg and Gall model. The subjects of this research were 20 class IV students. Data collection techniques use technical tests (pretest and posttest); and non-test techniques (observation, interviews, questionnaires). Initial data analysis technique with normality test; final data analysis using the T test and N-Gain test. The results of this research show: Evaluation of learning based on Automatic Assessment via Quizizz Paper Mode with components of questions, answers, question stimuli (images, videos, audio and tables), scores and duration of work with MOTS and HOTS cognitive levels; The results of the feasibility test for material experts and media experts are in the very feasible category; Effectiveness is seen from the pretest and posttest results. The T test results show Sig. (2-tailed) 0.000 <0.05. N-Gain score is 0.70 in the high category. The conclusion of this research is that the development of learning evaluation based on Automatic Assessment through Quizizz Paper Mode has been successfully developed, is very feasible, and is effective in improving the cognitive learning outcomes of class IV students.